Evolución de las técnicas de riego agrícola en Ecuador desde la civilización Inca hasta la actualidad - Reina Muñoz, Vanessa Johana (2024)
The present degree project addresses the topic of the evolution of agricultural irrigation techniques in Ecuador, focusing on the period from the Inca civilization to the present day. In order to describe the irrigation techniques used by the Incas in Ecuadorian territory, a thorough documentary historical analysis was conducted, allowing for a detailed understanding of the innovative irrigation practices implemented by this ancient civilization. A comprehensive compilation of current irrigation techniques and technologies used in Ecuador was carried out, with a particular focus on their impact on agricultural productivity. This study revealed significant advances in irrigation, including the development of modern drip and micro-sprinkler irrigation systems, as well as the increasing use of sensors and digital technologies to monitor and optimize water use in agriculture. The results obtained show a clear evolution in agricultural irrigation techniques in Ecuador, from the ancestral methods used by the Incas to the modern technologies employed today. As a result of this study, opportunities were identified to continue improving agricultural irrigation practices in Ecuador, especially regarding the integration of sustainable technologies and the promotion of ancestral knowledge about water management. It is recommended to continue researching and promoting responsible water use in agriculture, as well as promoting the preservation and revitalization of traditional irrigation techniques that have proven effective over time. It is concluded that the evolution of irrigation in Ecuador combines ancestral wisdom with modern technologies, from Inca practices to contemporary drip and sprinkler systems, improving water use efficiency in current agriculture.